Efeitos do laser de baixa intensidade na fotobiomodulação óssea após exodontia de molares em ratos espontaneamente hipertensos - Ramos, Giuliana Giovinazzo Anselmo (2016)
Systemic Arterial Hypertension (SAH) is considered as a polygenic, multifactorial syndrome, due to environmental, vascular, hormonal, renal and neural factors, affecting 1 in 3 adults over 65 years. There is an association between hypertensive individuals and reduced bone mineral density. Biostimulation with low intensity laser (LBI) has anti-inflammatory activity, accelerates the healing of bone defects in vivo and in vitro, stimulates blood flow, recruitment and activation of osteoblasts, osteosynthesis, and decreased osteoclastic activity. The hypothesis of this work is that photobiomodulation with LBI improves bone repair after exodontia in hypertensive rats. For the study, 24 female spontaneously hypertensive SHR rats (200-250 g) were used in which the right and left lower molars were extracted. The left alveolus was the control and the right one received the laser therapy (Therapy XT, DMC, São Carlos, Brazil), according to the following parameters: ƛ: 808 (± 10) nm, P = 100 mW, beam area: 0.126 cm2, time = 40 seconds, total energy = 4 J, power density = 0.8 W/cm2, energy density 32 J/cm2. Two applications were performed, one in the immediate postoperative period and the other on day 7. On days 7, 14, 30 and 60 the animals were euthanized and the mandible fragments sent for decalcification, paraffin inclusion, staining with hematoxylin & eosin and Mallory’s trichrome. The samples were evaluated by a pathologist without knowledge of the groups, who analyzed the presence and type of inflammation, necrosis, bacteria, epithelialization, neoformed bone area and number of osteocytes. The data were evaluated with t-test (SPSS v23, IBM) and there was no statistical difference between the groups in any of the parameters evaluated. It is concluded that under the conditions of the study, the application of LBI did not interfere in the bone repair of alveoli of spontaneously hypertensive rats.